FIDUCIARY GUARANTEE IN SHARIA FINANCING: ANALYSIS OF HARMONY IN THE PRINCIPLES OF MAQOSID SHARIA - Nur Sholikhah, Siti; cita devi, adinda rida; Azzahra, Nazwa; Amin, Sodiqul; Musadad, Ahmad (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2025)
Fiduciary guarantees serve as a significant legal instrument in Sharia-based financing, particularly in securing the interests of financial institutions while facilitating access to credit for customers. However, their implementation often raises concerns regarding consistency with the core principles of Maqasid Sharia, which aim to preserve religion (din), life (nafs), intellect (‘aql), lineage (nasl), and wealth (mal). This study employs a quantitative descriptive method to analyze the extent to which fiduciary guarantees align with these principles, particularly in protecting assets just and balanced. Data were collected through structured questionnaires distributed to Sharia financial institutions and their customers, then analyzed to evaluate the compatibility of fiduciary mechanisms with Islamic values, especially fairness and the balance of rights and obligations. The findings suggest that while fiduciary guarantees have the potential to support asset protection by Sharia, several procedural and ethical aspects require further optimization to meet the objectives of Maqasid Sharia fully. This study is expected to provide insights that contribute to the refinement of Sharia financing practices and the development of legal frameworks in Indonesia.